Pelmatellus amicorum Delgado and Ruiz-Tapiador (Coleoptera: Carabidae), a New Species from the Andean Altiplano of Peru - Delgado Mamani, Pedro Ernesto (2020)
A new species of ground beetle, Pelmatellus amicorum Delgado and Ruiz-Tapiador (Coleoptera: Carabidae), from the Andean Altiplano of Peru is described. The state of knowledge of the genus and the relationship of the new species with known congeneric species are reviewed.